Interannual patterns of variation in concentrations of trace elements in arms of Octopus vulgaris - Seixas, Sónia (2010)
Concentrations of essential (copper, iron, manganese, selenium, andzinc) andnon-essential (arsenic, cadmium, mercury, andlead ) trace elements were measuredin arms of Octopus vulgaris. The cephalopods were sampled from commercial fishery landings at two sites on the Portuguese coast in spring 2002 and 2003. Mercury was determined using an Advanced Mercury Analyser Spectrophotometer (AMAS) and other trace elements were measured using inductively coupled plasma-atomic emission spectrometry (ICP-AES). Since high levels of arsenic were detected, identification of the forms present was carriedout using high performance liquid chromatography (HPLC) followedby ICP-MS. Mean concentrations of trace elements analysedw ere in the following order: As > Zn > Fe > Cu Cd> Pb > Se >Mn Hg. The results of speciation of arsenic demonstrate that virtually all arsenic was in the arsenobetaine form, which is the less toxic form. The concentrations of several trace elements were generally high in samples from Viana in 2002. Cadmium concentrations were above the legal limit for human consumption in samples from Viana in 2002 and two of these animals alsohadleadconcentrations that exceededlegal limits.Mercury appearedin all samples but levelswerewithin legally defined safe limits.No relationshipwas detected between trace element concentrations and size ormaturity of octopus.